The Analysis of Production Costs of Laying Hen Farms Using Semi Self-Mixing and Total Self-Mixing Feeds in Blitar Regency, East Java - R. Afandi; B. Hartono; I. Djunaidi (Tropical Animal Science Journal, 2020)
Feed plays an important role in determining the success of livestock businesses and also as a significant cost factor. Feed contributes 60%-80% of the total production costs. The types of feed could have different effects on the cost, efficiency, and productivity of livestock business. Some laying-hen farmers in Blitar District use two kinds of feed, semi self-mixed feed, and total self-mixed feed. This study was conducted to compare the use of two types of feed on the net revenue of laying hen farmers in Blitar Regency. The research used the survey method. The sample in this research consisted of 100 laying-hen farmers in Blitar Regency, 50 of them used semi self-mixing feed and the rest used total self-mixing feed. Data were collected from several laying hen farms in Blitar Regency with a survey method. All data were then analyzed both qualitatively and quantitatively. The average feed price of semi self-mixed feed and total self-mixed feeds were IDR 5,143.38 and IDR 4,854.91 per kg, respectively. The results showed that the feed price, cost of medication/vaccine, the amount of feed, and egg production for semi self-mixed feed farmers had significant effects on the net revenue of the farmer (p<0.05), with the average net revenue being IDR 12,785,471.68 per 1,000 birds/period. Whereas for total self-mixed feed, the medication/vaccine cost and feed amount had significant effects on the net revenue of the farmer (p<0.05), with the average net revenue being IDR 18,467,373.76 per 1,000 birds/period. As a conclusion, the total self-mixed feed showed more optimal net revenue of laying hen than semi self-mixed feed.